The influence of leadership effectiveness, motivation, and compensation on job engagement with job satisfaction as an intervening variable - Riska Novialni, Riska; Pranitasari, Diah; Sakti, Indra (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2024)
Recovery Version (See for detail) This study aims to assess the impact of leadership effectiveness, work motivation, and compensation on employee job satisfaction, as well as their influence on job engagement at PT. Beautiful Gift Partners. A survey method with a quantitative approach was employed, targeting 200 employees from the company. Using the Slovin formula, 133 respondents were selected. Statistical analyses included validity and reliability tests, path analysis, partial hypothesis testing (t-test), and the Sobel test. Findings reveal that leadership effectiveness positively influences job satisfaction, while work motivation does not. Compensation positively affects job satisfaction, yet job satisfaction does not significantly impact work engagement. Furthermore, leadership effectiveness, work motivation, and compensation do not directly influence work engagement through job satisfaction. Article Information:Received 1/31/2023 / Revised 4/23/2024 / Accepted 4/23/2024 / Online First 5/1/2024